Pengembangan Teknologi Tepat Guna Sprayer Hybrid Menggunakan Panel Surya di Desa Jipang, Kecamatan Cepu, Kabupaten Blora - Agus Sulistiawan; Mohammad Anshori; Azhary, Taufik; Uud Setiyo Mujiharto; Ahmad Taufiqqurohman; Mohammad Agung Prayitno; Faiz Ardiansyah (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2025)
The development of technology in the modern era is very rapid, so it can help and solve many problems in various fields, one of which is agriculture. A sprayer is one of the pieces of equipment in agriculture that is used to spray pesticides as an eradicator of pests and diseases in plants. Jipang Village, Cepu District, Blora Regency already has sufficient agricultural infrastructure, but it is still limited in terms of the use of modern agricultural technology. This can slow down work because many villagers still use manual spraying techniques. The use of electric sprayers is a solution but has a battery-dependent durability, where the longer it is used, the faster the power runs out. This results in the work of farmers who will be hampered and not optimal because it takes additional time to charge the battery. Therefore, a power source that is unlimited in supply, non-polluting, and safe is sought. The development of appropriate hybrid sprayer technology using solar panels is one option that can be chosen because it has low operational and maintenance costs, as well as being environmentally friendly and renewable energy. The method used in this activity is socialization, training, and mentoring, as well as monitoring of farmers in Jipang Village, Cepu District, Blora Regency, starting from the assembly to the use of hybrid sprayers using solar panels. The results of this community service activity (PKM) show that farmers have been able to assemble and operate modern spraying equipment in accordance with technological developments so that they can save time and energy needed in spraying after using solar panels on electric sprayers. This is very desirable in order to help farmers in overcoming the efficiency of time and energy in working by utilizing renewable energy that is more effective and efficient, namely by using sunlight. In addition, farmers also get a better understanding of the innovations and technological developments that can be used in agriculture; spraying shows more even results and can save the use of insecticides and can avoid farmers from prolonged exposure to insecticides. Keywords: Sprayer, Solar Panel, Renewable Energy